Mahabbah Dalam Tasawuf Rabi'ah Al-Adawiyah : Apresiasi Atas Rintisan Mistik Sejati dalam Islam - Ach Maimun (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
This paper aims to discuss on Rabi’ah al-'Adawiyah’s mahabbah teaching as the beginning pattern of Sufism, In the f irst century of Islam, the Sufism life or known as the spiritual life was based on fear (khauf) which then expanded become the resignation (tawakkal) to the God. In the second century, the meaning of mahabbah or called the divine love was raised and changed toward extreme pole. The figure who starting the change of mahabbah meaning from rational one to the emotional one was Rabi’ah al-‘Adawiyah. Mahabbah in Sufism discourse is the highest degree in Rabi’ah teaching. The value of pure love in Sufism life granted the big change toward of next path of Sufism. All Sufi referred to the sincerity found in love of Rabi'ah. Rabi’ah made easy the path of al-Bisthami, al-Hallaj, al-Ghazali, Ibnu Arabi. Even Jalal al-Din al-Rumi put his art works and Sufism experiences in mahabbah as for Rabi’ah.